Parallelization of a quantum-classic hybrid model for Nanoscale Semiconductor devices - Salas, Oscar (2011)
The expensive reengineering of the sequential software and the difficult parallel programming are two of the many technical and economic obstacles to the wide use of HPC. We investigate the chance to improve in a rapid way the performance of a numerical serial code for the simulation of the transport of a charged carriers in a Double-Gate MOSFET. We introduce the Drift-Diffusion-Schrödinger-Poisson (DDSP) model and we study a rapid parallelization strategy of the numerical procedure on shared memory architectures.